Malaria profiles and challenges in artemisinin resistance containment in Myanmar - Thet Wai Nwe; Tin Oo; Khin Thet Wai; Shuisen Zhou; Johan van Griensven; Palanivel Chinnakali; Safieh Shah; Aung Thi (BMC, 2017)
Abstract Background This study examined evolving malaria profiles from January, 2010 to December, 2014 to evaluate achievements and challenges of implementing measures to prevent and control spread of artemisinin resistance in Myanmar. Methods Using National Malaria Control Programme (NMCP) data, a cross-sectional descriptive study of 52 townships in artemisinin-resistant containment areas in Myanmar was conducted. Annual program data were analysed, and trends over time are graphically presented. Results In the 52 study townships populated by 8.7 million inhabitants, malaria incidence showed a decreasing trend from 10.54 per 1 000 population in 2010 to 2.53 in 2014, and malaria mortalities also decreased from 1.83 per 100 000 population in 2010 to 0.17 in 2014. The proportion of confirmed to total tested malaria cases also decreased from 6 to 1%, while identification of cases improved. All cases from all parasites species, including Plasmodium falciparum, decreased. Coverage of LLIN (long-lasting insecticidal net)/ITN (insecticide-treated mosquito nets) and indoor residual spraying (IRS) was high in targeted areas with at-risk persons, even though the total population was not covered. In addition to passive case detection (PCD), active case detection (ACD) was conducted in hard-to-reach areas and worksites where mobile migrant populations were present. ACD improved in most areas from 2012 to 2014, but continues to need to be strengthened. Conclusions The findings provide useful data on the malaria situation in artemisinin-resistant initiative areas, which may be useful for the NMCP to meet its elimination goal. These profiles could contribute to better planning, implementation, and evaluation of intervention activities.